Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13027-020-00342-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between oncogenic human papillomavirus type 16 and Killian polyp

Abstract: Background Killian polyp (KP) is a benign lesion that arises from the maxillary sinus. The etiology of KP is unknown. The aim of this study was to investigate the potential involvement of human papilloma- (HPV) and polyoma-viruses (HPyV) infections in the onset of KP. Methods DNA from antral (n = 14) and nasal (n = 14) KP fractions were analyzed for HPV and HPyV sequences, genotypes, viral DNA load and physical status along with expression of viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Over the years, with the development of molecular technology/methods (Park et al, 2012;Tognon et al, 2015;Rotondo et al, 2018bRotondo et al, , 2020aMazzoni et al, 2020;Preti et al, 2020;Oton-Gonzalez et al, 2021), many studies have investigated the relationship between DNA methylation and male infertility on a genome-wide scale by employing high-throughput techniques (Houshdaran et al, 2007;Ferfouri et al, 2013;Schütte et al, 2013;Camprubí et al, 2016;Du et al, 2016;Jenkins et al, 2016a,b;Laqqan et al, 2017a;Lee et al, 2019). The first array-wide analysis was performed by Houshdaran et al (2007) highlighting improper DNA methylation at repetitive element satellite 2, H-RAS, neurotrophin 3, paired-box gene 8, and Stratifin, 3 -nucleotidase, and metallothionein 1A genes in semen samples with abnormal sperm concentration, motility, and morphology.…”
Section: High-throughput Techniques For Dna Methylome Investigationmentioning
confidence: 99%
“…Over the years, with the development of molecular technology/methods (Park et al, 2012;Tognon et al, 2015;Rotondo et al, 2018bRotondo et al, , 2020aMazzoni et al, 2020;Preti et al, 2020;Oton-Gonzalez et al, 2021), many studies have investigated the relationship between DNA methylation and male infertility on a genome-wide scale by employing high-throughput techniques (Houshdaran et al, 2007;Ferfouri et al, 2013;Schütte et al, 2013;Camprubí et al, 2016;Du et al, 2016;Jenkins et al, 2016a,b;Laqqan et al, 2017a;Lee et al, 2019). The first array-wide analysis was performed by Houshdaran et al (2007) highlighting improper DNA methylation at repetitive element satellite 2, H-RAS, neurotrophin 3, paired-box gene 8, and Stratifin, 3 -nucleotidase, and metallothionein 1A genes in semen samples with abnormal sperm concentration, motility, and morphology.…”
Section: High-throughput Techniques For Dna Methylome Investigationmentioning
confidence: 99%
“…Indeed, several works reported the presence of HPV16 DNA/mRNA in nasal/Killian polyps nearby the maxillary sinus region. These studies suggest that, HPV16 can potentially drive malignant transformation of the oral region following nasal polyp infection [16,17]. The HPV molecular test aims to search for viral DNA sequences in tissues.…”
Section: The Human Papillomaviruses (Hpvs)mentioning
confidence: 99%
“…However, there is no evidence claiming neoplastic transformation of KP, except reported incidents mimicking malignant transformation [ 62 ]. It is difficult to report HPV carcinogenesis in KP, as patients remove them immediately after presentation, and carcinogenic events caused by HPV infection require longer to develop and to be detected [ 63 ]. A study by Knör and colleagues indicated the existence of HPV in nasal and antrochoanal polyps.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…Similarly, Oton-Gonzalez et al (2021) reported the presence of low HPV-16 DNA amounts in both episomal and integrated forms in antral KP. However, they did not report viral expression of E2, E5, E6, and E7 sequences in the HPV-positive KP samples [ 63 ].…”
Section: Human Papillomavirusmentioning
confidence: 99%